Herbivory of Atta cephalotes (Hymenoptera: Myrmicinae) on three plant substrates - RODRÍGUEZ-G., JHONATTAN; CALLE-D., ZORAIDA; MONTOYA-LERMA, JAMES (Revista Colombiana de Entomología, 2008)
A recent study suggests a significant reduction of herbivory by the leaf cutting ant, Atta cephalotes, in plantations of the pioneer tree (Montanoa quadrangularis (Asteraceae)) when associated and fertilized with green foliage of the Mexican sunflower (Tithonia diversifolia (Asteraceae)). These observations suggest a dissuasive effect of this plant on foraging by the ants. In order to test this hypothesis, under laboratory conditions seven experimental colonies of A. cephalotes were offered three plant diets to choose among (i.e.: foliage of mango, Mangifera indica (Anacardiaceae), yellow candle Pachystachys lutea (Nees) (Anacardiaceae) and T. diversifolia (Asteraceae) during three periods of 21 days. Consumption was estimated by measuring and weighing the foliage before and after being deposited into each colony. In the first assay, there was a significant (P < 0.05) preference for mango while the consumption of T. diversifolia was irregular after the first day of experimentation and had the lowest percentage. In the two following studies no significant differences (P > 0.5) were observed in the percent consumption of the diets, although mango foliage was the first to be consumed by the ants. The results allow us to conclude that under the experimental conditions, A. cephalotes has a greater preference for mango foliage, but when the availability of this resource is minimal, they forage in an opportunistic way on other resources such as T. diversifolia, even if these are not preferred. The study provides more evidence that this plant is not attractive to leaf-cutting ants.